A THEORETICAL ANALYSIS OF THE ROLE OF FORENSIC ACCOUNTING IN FRAUD PREVENTION IN THE DIGITAL ERA - Maureen Joanna Finny; Sam Hermansyah (CV. Fahr Publishing, 2024)
This study aims to develop a theoretical framework that enhances the role of forensic accounting in preventing financial fraud within increasingly digitized financial environments. With the rise of cyber-enabled fraud schemes such as identity spoofing, algorithmic manipulation, and blockchain-based laundering, traditional models like the fraud triangle and fraud diamond are no longer sufficient as standalone tools. To address this, the research applies a qualitative library research method, utilizing a systematic literature review from academic databases, professional reports, and recent scholarly publications (2018–2024). The analysis reveals that while forensic accounting theories remain relevant, they require integration with digital tools such as AI, big data analytics, and blockchain to detect and prevent modern fraud effectively. One of the study’s key findings is the lack of standardized protocols and cross-disciplinary frameworks that merge behavioral fraud theory with real-time forensic technologies. The novelty of this research lies in its proposal to reposition forensic accounting from a reactive to a proactive model by synthesizing insights from accounting, IT governance, and risk management. Furthermore, the study emphasizes the need to modernize forensic education and regulatory infrastructure, particularly in developing economies, to close the implementation gap. In conclusion, this research contributes a comprehensive and adaptive theoretical foundation that aligns forensic accounting with the dynamics of digital financial ecosystems, offering practical relevance for academics, practitioners, and policymakers in addressing global fraud challenges.